Off-the-shelf thermoluminescent silica glass media for use in medical diagnostic dosimetry applications. (December 2021) - Alyahyawi, Amjad; Alanazi, Abdulaziz H.; Almurayshid, Mansour; Alshahri, Saad; Almeshari, Meshari; Bradley, D.A.
Abstract: In respect of radiation exposure assessments, thermoluminescent dosimeters (TLD) represent a notable and important subset of passive detector technology, gaining widespread use over a period of many decades, not least for medical applications. TLDs are available in a range of physical and chemical forms, in particular the popularity of phosphor-based commercial products arising from features that include availability down to low mm dimensions, soft-tissue equivalence in some cases, and relatively low TL fading. Novel doped silica glass TL material fabricated as fibres also offer favourable responses, recent developments in co-doping leading to their ability to also provide for diagnostic radiology applications, adding to the attractive features of being impervious to water, of good sensitivity, and generally offering wide dynamic range. Thus said, doping and fibre fabrication involve relatively high costs. Accordingly, herein exploratory investigations are made of the cost-effective colourless silica-based glass medium from which marbles are made, reduced into chip form for ease of application, examining sensitivity to dose. In particular, the study focuses on the computerised tomography clinical application regime, 80- to 140 kVp, with excellent response being shown for doses within the range 2- to 50 mGy. Highlights: Off-the-shelf thermoluminescent silica glass media. Easily formed into cost effective convenient chip dosimeters. Elemental and glow curve analysis points to soda-lime glass. Tested in clinical CT dosimetry applications regime.